The Visconde ruling media go soft on Webb - Mangilit, Rupert Francis D. (PJR Reports, 2011)
The Vizconde Ruling Media Go Soft on Webb by Rupert Francis D. Mangilit with a report from Kathryn Roja G. Raymundo Covering Military Corruption Investigative and Explanatory Pieces Led the Way by Hector Bryant L. Macale Media Coverage of the Reyes Suicide Breaking All the Rules by Kathryn Roja G.